CRUDE OIL HE AND AR ISOTOPIC CHARACTERISTICS AND THEIR GEOCHEMICAL SIGNIFICANCE: AN EXAMPLE FROM THE GANGXI OIL FIELD IN THE HUANGHUA DEPRESSION - Zhang X.; Ma L.; Sun M.; Li X.; Song C.; Chen J.; Tu J. (My University, 2005)
Sampled from the Gangxi oil field in the Huanghua depression, Bohaiwan Basin, the crude oil He and Ar isotopic compositions and their geochemical significance were investigated. The result shows that i) the 3He/4He values of the six oil samples free from air contamination indicate a mantle helium contribution ranging between 13.9% and 32.8% and averaging 24.1%, which means that the Gangxi oil field once had a tectonic background of the mantle-derived helium input and higher geothermal flow with an average of 75.0 mWm-2; ii) deduced from the 40A/36Ar aging effect the Gangxi oil should be derived from the Tertiary; iii) water injection is the main reason for the air contamination for the Gangxi oil noble gases and the relations between 3He/4He and 3He/20Ne as well as 40A/36Ar and 4He/20Ne are of an applicative potential in estimating the water injection effect and the connectivity of producing formations. The search for the crude oil He and Ar isotopes provides a new approach to inferring natural gas and oil sources, tectonic backgrounds, geothermal flow and water injection effect.
Keywords: CRUDE OIL; GANGXI OIL FIELD; HUANGHUA DEPRESSION; NOBLE GAS TRACING